Methodology for the design of leading edge devices applied to variable camber - Lajux, Vincent (Cranfield University, 2007)
This thesis will describe a new and innovative way of approaching the design of leading edge devices; this done using new tools and state of the art software. This innovative design methodology for leading edge devices has a special focus on the application of variable camber technology. A precise description is given of the way to check that methodology acts as a means of validation. A case study shows how to apply this methodology and examines a variable camber application. This case study provides the basis for the understanding of how to apply the design methodology and give results generated from its different parts. An analysis of the structure and aerodynamic performances of a new type of leading edge device was performed in addition to moving the overall design towards an optimum solution in term of mass, reliability and cost. The case study is showing that using a variable camber leading edge device could be beneficial as it proves a better option than more classical concepts. Some of the results show that the aerodynamics implications of using this type of device at the leading edge can be beneficial in cruise and also during take off and landing. Also on the structural side of things, it is possible to see that the deployment trajectory as been optimised to fit to the required trajectory and the structure is able to resist critical loading. Finally there is a discussion on the obtained results and on the overall methodology to make conclusions on the overall meaning of this research and the possible impact of the new design methodology as well as implication on the design of variable camber leading edge devices.